Small Primary Schools in Rural Wales: Frameworks of Collaboration - Ina Williams; Richard Thorpe (Journal of Research in Rural Education, 1998)
This paper discusses the ways in which small rural schools in Wales are collaborating, and how such collaboration is supported by the education authorities. We describe how recent legislation has led to the reorganisation of education authorities in Wales and how this, together with new demands and reduced resources in turn, has affected their support for small rural schools. These schools have in the past belonged to geographically determined groupings, and in-service training for teachers has taken place through these groupings. We show how five of the new education authorities have met their responsibilities to small rural schools through different models ofsupport for collaboration. Three frameworks are identified, which reveal different degrees ofstructure and control ofschool groupings and their agendas. The relative effectiveness ofthese frameworks in providingfor teachers training needs is discussed, and our general conclusion is that freedom and teacher ownership within a defined overall structure is most effective.